Dft Study Of Few-Layer Graphene-Metal Composites (Physical Sciences and Technology, 2016)
Graphene and it’s few-layer configurations are the multi-functional materials for a wide range applications. Particularly, they can be used in production of composites, based on metal, ceramic, polymer matrices, as elements of reinforcement. Taking into consideration the fact of some difficulties of graphene application, such as surface chemical inertness and sliding between the layers of graphene sheets under stressed state, here we perform the computer simulation study of radiation defects which make possible the formation of stable graphene-metal structures. Performed quantum mechanical calculations revealed that that few-layer graphene – metal (Cu, Al, Li) fast bonds can be induced due to production of radiation structural defects.
Keywords: Key words; Graphene; radation defects; graphene metal structure; strnctural defects PACS numbers; 81.05.ue; 61.72.–y